Visions at war? : EAS in the regional architecture debate - Tan, See Seng (2012)
Three visions of regional architecture in East Asia – which can be referred to as the “Canberra”, “Washington” and “Singapore” schools – are in contention. What are their implications for the newly enlarged East Asia Summit?